DEIXIS IN FRANK OCEAN’S BLONDE ALBUM : CONSTRUCTING EMOTION AND INDENTITY THROUGH LYRICS - Situmorang, Sondang Indah Clara; Yastanti, Unpris (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2025)
This study examines the pragmatic realization of deixis in five selected tracks from Frank Ocean’s Blonde album. The analysis focuses on person, temporal, and spatial deixis to determine how deictic expressions encode emotional stance, identity construction, and relational positioning within the lyrics. The research applies a qualitative descriptive methods , with data obtained through lyric transcription and interpreted using contextual pragmatic analysis.The results indicate that person deixis, especially the oscillation between “I,” “you,” and “we,” frames asymmetrical emotional relations and reveals shifts in intimacy, vulnerability, and self-awareness. Temporal deixis captures the interplay between past memory, present instability, and imagined futures, exposing fluctuating psychological states. Meanwhile, spatial deixis functions metaphorically to mark emotional spaces rather than physical settings, signifying belonging, transition, and internal refuge.Overall, deixis in Blonde operates not merely as a referential device but as a stylistic mechanism that articulates affective complexity and identity negotiation. This research contributes to pragmatic stylistics by demonstrating how deictic strategies in song lyrics can index psychological depth and relational meaning, thereby offering a basis for further linguistic examinations of musical discourse.